Optimizing the Four-Wheel Patrol of the Sabhara Unit in Preventing Theft at the Indragiri Hulu Police Department - Yoga Fattur Rahman (Advances in Police Science Research Journal, 2021)
This research is motivated by the existence of cases of motor vehicle theft (curanmor) that occurred in Indragiri Hulu Regency with a fairly high number of incidents. The four-wheeled patrol unit of the Sabhara Polres Indragiri Hulu has carried out preventive efforts by carrying out routine patrols to prevent theft, but the crime of theft still occurs and has increased, especially in 2020. This study was conducted to examine the implementation of the four-wheeled patrol unit of Sabhara and its optimization. which must be carried out by the four-wheeled patrol unit of the Indragiri Hulu District Police Sabhara. This study uses previous research, theories and concepts. This study also uses a qualitative approach, the data collection techniques used are observation, interviews, and document studies. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of the study found that the implementation of the four-wheel patrol unit of the Indragiri Hulu District Police was still considered not optimal. The influencing factors are that there are still many personnel who have not attended vocational education and development education, as well as the lack of a fuel budget for patrols that is not in accordance with the area of ​​Indragiri Hulu Regency. Based on the results of the study, the researchers suggest increasing the intensity of patrolling, as well as optimizing the use of the SIPEKA application by members and the public to determine the points prone to crime.